Changes in the life of Germans in St. Petersburg in the late 19th – early 20th century: Изменения в жизни санкт-петербургских немцев в конце XIX – начале ХХ века - Sinko, Galina; Sidnenko, Tatyana; Erokhina, Ol’ga (Przegląd Wschodnioeuropejski, 2021)
The subject of this paper is an overview of changes in the material and spiritual life of Germans living in St. Petersburg in the late 19th – early 20th century. The overview of various facets of life of German population of St. Petersburg makes it possible to comprehensively address the problem of transformation of the State nationalities policy toward the largest ethnic diaspora in the Imperial Capital. The research work of Russian and foreign scholars became the theoretical framework for the article that enabled to ensure continuity of historical analysis. This study used a problematic and chronological approach to review the dynamics of state legislative initiatives related to in relation to the German community of St. Petersburg. The legislative acts issued in the Russian Empire during the period under study to toughen up the legal regulations governing the life of Russian Germans served as the factual basis of the overview. The conclusions drawn in the paper give a better idea of general trends in the nationalities policy of the Russian state in the midst of the most important domestic and international events of the late 19th and early 20th century.